2022
DOI: 10.1038/s41467-022-30727-4
|View full text |Cite
|
Sign up to set email alerts
|

Flood exposure and poverty in 188 countries

Abstract: Flooding is among the most prevalent natural hazards, with particularly disastrous impacts in low-income countries. This study presents global estimates of the number of people exposed to high flood risks in interaction with poverty. It finds that 1.81 billion people (23% of world population) are directly exposed to 1-in-100-year floods. Of these, 1.24 billion are located in South and East Asia, where China (395 million) and India (390 million) account for over one-third of global exposure. Low- and middle-inc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
144
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 328 publications
(148 citation statements)
references
References 41 publications
2
144
0
2
Order By: Relevance
“…They do not capture pluvial flood hazards and flooding along secondary rivers, drastically underestimating exposure 35,37,38 . One study using coarse flood data projected that the global number of flood-exposed people will reach 1.3 billion by 2050 3937 but a more recent high-resolution study showed that this threshold has already been exceeded by at least 39% in 2020 39 . This illustrates the importance of using high-resolution data to capture the highly localized nature of flood hazards and people's tendency to avoid settling in the most hazardous locations 355 .…”
Section: Existing Evidencementioning
confidence: 99%
“…They do not capture pluvial flood hazards and flooding along secondary rivers, drastically underestimating exposure 35,37,38 . One study using coarse flood data projected that the global number of flood-exposed people will reach 1.3 billion by 2050 3937 but a more recent high-resolution study showed that this threshold has already been exceeded by at least 39% in 2020 39 . This illustrates the importance of using high-resolution data to capture the highly localized nature of flood hazards and people's tendency to avoid settling in the most hazardous locations 355 .…”
Section: Existing Evidencementioning
confidence: 99%
“…For example, Rentschler et al. found that of the 1.81 billion people in the world who are exposed to significant flood risk, South and East Asia account for 69% (1.24 billion) of the exposed population (Rentschler et al., 2022). Beyond urban centers, rural regions are also at risk; many rural communities are dependent on climate‐sensitive resources that can impact their livelihoods and way of life (Pulhin et al., 2010).…”
Section: Drivers Of Black Elephant Risks Of Asiamentioning
confidence: 99%
“…With rapid industrialization and urbanization in the region, an increasing proportion of people live in crowded cities, oftentimes in places comprised of unregulated building construction (Wood, 2018). These increasingly dense urban areas are often exposed to a diverse range of natural hazards: for example, located in regions of high seismic hazard and/or near coastal regions and large rivers, prone to tsunami, storm, and flood hazards (Rentschler et al, 2022;Wood, 2018). For example, Rentschler et al found that of the 1.81 billion people in the world who are exposed to significant flood risk, South and East Asia account for 69% (1.24 billion) of the exposed population (Rentschler et al, 2022).…”
Section: Drivers Of Black Elephant Risks Of Asiamentioning
confidence: 99%
“…We focused on water-related disasters, such as floods, tornadoes, tsunamis, and hurricanes, among many others, given their increasing frequency and severity in the most vulnerable low-and middle-income countries (Hallegatte et al, 2013;Edmonds et al, 2020;Rentschler et al, 2022). Despite substantial losses caused by disasters, a significant population is unable to leave disaster-prone regions (Tellman et al, 2021) for socioeconomic and political reasons (Hunter, 2005;Raker, 2020;Lin et al, 2021;Henkel et al, 2022).…”
Section: Introductionmentioning
confidence: 99%